2015
DOI: 10.1186/s13071-015-0862-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of reference genes for insect olfaction studies

Abstract: BackgroundQuantitative reverse transcription PCR (qRT-PCR) is a robust and accessible method to assay gene expression and to infer gene regulation. Being a chain of procedures, this technique is subject to systematic error due to biological and technical limitations mainly set by the starting material and downstream procedures. Thus, rigorous data normalization is critical to grant reliability and repeatability of gene expression quantification by qRT-PCR. A number of ‘housekeeping genes’, involved in basic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 66 publications
1
31
0
2
Order By: Relevance
“…A set of candidate reference genes (Table 1) was selected because they were all previously used for qPCR normalization in triatomines (Majerowicz et al, 2011;Paim et al, 2012) and other insect species (Scharlaken et al, 2008;Lord et al, 2010;Ling and Salvaterra, 2011;Ponton et al, 2011). Table 2 lists all reference factors calculated as the geometric means of the most stable combinations of these genes (Omondi et al, 2015b), used to evaluate changes in gene expression in the antennae of R. prolixus. The sequences of reference and target genes (RproOrco, RproIR8a, RproIR25a, and RproIR76b) were identified in the R. prolixus genome (available on www.vectorbase.org/organisms/rhodnius-prolixus) using a local tBLASTn algorithm (Altschul et al, 1997).…”
Section: Reference Genes and R Prolixus Or And Ir Coreceptorsmentioning
confidence: 99%
“…A set of candidate reference genes (Table 1) was selected because they were all previously used for qPCR normalization in triatomines (Majerowicz et al, 2011;Paim et al, 2012) and other insect species (Scharlaken et al, 2008;Lord et al, 2010;Ling and Salvaterra, 2011;Ponton et al, 2011). Table 2 lists all reference factors calculated as the geometric means of the most stable combinations of these genes (Omondi et al, 2015b), used to evaluate changes in gene expression in the antennae of R. prolixus. The sequences of reference and target genes (RproOrco, RproIR8a, RproIR25a, and RproIR76b) were identified in the R. prolixus genome (available on www.vectorbase.org/organisms/rhodnius-prolixus) using a local tBLASTn algorithm (Altschul et al, 1997).…”
Section: Reference Genes and R Prolixus Or And Ir Coreceptorsmentioning
confidence: 99%
“…In agreement with our findings, previous studies have also demonstrated that 1, 8‐Cineole is highly repellent against a diverse range of agricultural and medical pests . S ‐(−)‐ cis ‐Verbenol is a ubiquitously terpenoid volatile compound present in many plants and proved to be repellent for different insect pests . Behavioral responses of first‐instar nymphs of Chagas disease vectors, Rhodnius prolixus and Triatoma infestans (Heteroptera: Reduviidae) to several monoterpenes including S ‐(−)‐ cis ‐Verbenol were tested.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58] S-(−)-cis-Verbenol is a ubiquitously terpenoid volatile compound present in many plants and proved to be repellent for different insect pests. [59][60][61][62] Behavioral responses of first-instar nymphs of Chagas disease vectors, Rhodnius prolixus and Triatoma infestans (Heteroptera: Reduviidae) to several monoterpenes including S-(−)-cis-Verbenol were tested. All tested chemicals were repellent for T. infestans and their efficiencies were as equal as DEET.…”
Section: Discussionmentioning
confidence: 99%
“…Todas las muestras se procesaron siguiendo las especificaciones detalladas en anexo para extracción de ARN y síntesis de ADNc. Se utilizaron como genes de referencia β-tubulina (β-tub) y factor de elongación-1 (RpEf1), que demostraron ser estables en R. prolixus bajo distintas condiciones (Majerowicz, Alves-Bezerra et al 2011;Omondi, Latorre-Estivalis et al 2015). La eficiencia de todos los primers utilizados en qRT-PCR fue evaluada a las concentraciones de molde: 1:2; 1:10 y 1:20 y un modelo de regresión lineal para determinarla.…”
Section: Extracción De Rna Y Síntesis De Cdnaunclassified
“…Debido a esto se determinó utilizar ambos genes como housekeeping, realizando un promedio de los resultados de cada uno utilizando una media geométrica (Majerowicz, Alves-Bezerra et al 2011;Omondi, Latorre-Estivalis et al 2015).…”
Section: Pcr Cuantitativa En Tiempo Realunclassified